HEAD AND FACIAL ANTHROPOMETRY FOR DETERMINING THE CRITICAL GLASSES FRAME DIMENSIONS - C. N. ROSYIDI; N. RIYANTI; I. IFTADI (Journal of Engineering Science and Technology, 2016)
Many products have been designed and developed to aid and support people in their daily activities. The products are created after a series of activities from generating ideas, converting the ideas into design, and bringing the design into a real product. Glasses consist of a sub-assembly and components namely a frame and a pair of lenses. The frame has three critical parts namely the rim, bridge width, and temple length. The aim of this research is to determine the head and facial anthropometry which can be used to find the critical glasses frame dimensions. The results of this research show that there are significant differences in the anthropometry between female and male. We proposed the same dimension for end piece and bridge for both female and male while the rim and temple dimension must be different between female and male.